Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Maximizing the phylogenetic diversity of seed banks - Kate E. Griffiths; Sharon T. Balding; John B. Dickie; Gwilym P. Lewis; Tim R. Pearce; Richard Grenyer (Conservation Biology, 2015)
Ex situ conservation efforts such as those of zoos, botanical gardens, and seed banks will form a vital complement to in situ conservation actions over the coming decades. It is therefore necessary to pay the same attention to the biological diversity represented in ex situ conservation facilities as is often paid to protected‐area networks. Building the phylogenetic diversity of ex situ collections will strengthen our capacity to respond to biodiversity loss. Since 2000, the Millennium Seed Bank Partnership has banked seed from 14% of the world's plant species. We assessed the taxonomic, geographic, and phylogenetic diversity of the Millennium Seed Bank collection of legumes (Leguminosae). We compared the collection with all known legume genera, their known geographic range (at country and regional levels), and a genus‐level phylogeny of the legume family constructed for this study. Over half the phylogenetic diversity of legumes at the genus level was represented in the Millennium Seed Bank. However, pragmatic prioritization of species of economic importance and endangerment has led to the banking of a less‐than‐optimal phylogenetic diversity and prioritization of range‐restricted species risks an underdispersed collection. The current state of the phylogenetic diversity of legumes in the Millennium Seed Bank could be substantially improved through the strategic banking of relatively few additional taxa. Our method draws on tools that are widely applied to in situ conservation planning, and it can be used to evaluate and improve the phylogenetic diversity of ex situ collections. Maximizar la Riqueza Filogenética de los Bancos de Semillas

The social network structure of a wild meerkat population: 2. Intragroup interactions - Joah R. Madden; Julian A. Drewe; Gareth P. Pearce; Tim H. Clutton-Brock (Behavioral Ecology and Sociobiology, 2009)